Evaluation of the Implementation of Educational Management Information Systems in Supporting Strategic Decision-Making in Higher Education - Ahmad, Iskandar (PT FORMOSA CENDEKIA GLOBAL, 2024)
Education Management Information Systems (EMIS) are essential for supporting strategic decision-making in higher education institutions. This study evaluates the implementation of EMIS through a review of 13 scholarly articles, focusing on its benefits, challenges, and strategic contributions. Findings indicate that EMIS improves efficiency, transparency, and accountability but faces obstacles such as resistance to change, inadequate infrastructure, and limited user training. The study emphasizes the need for stakeholder collaboration, data-driven decision-making, and integration with advanced technologies like big data analytics. By examining EMIS's strategic role beyond administrative tasks, this research offers actionable recommendations to optimize EMIS in achieving institutional goals